Effect of Particle Size of Waste Glass on Compressive Strength and Modulus of Rupture of Concrete Mix - Atwan, Dalia Shakir (Al-Nahrain Journal for Engineering Sciences, 2017)
Glass is an inert material which could be used and recycled many times. Several tons of waste glass (WG) are generated annually worldwide due to the rapid growth of the population and improvement in the standard of living. In this study, the WG was used and supplied with three different particle sizes; 600?m, 2.36 mm and 4.75mm and partially weight replaced of fine aggregate at ratios 10%, 20% and 30%. The effectiveness of that changes on compressive strength and modulus of rupture at ages 28 and 90 days for concrete specimens produced were studied. The results showed that compressive and modulus of rupture at all ages increased along with addition of WG as glass powder (GP). Moreover, the specimens containing 30% of GP replaced has the best results, also it is found at this percentage of GP, more beneficial and capable to increased compressive and flexural strength up to 18.64% and 5.87 % respectively at 28-day compared to reference specimen. Besides, the test results revealed that at a replacement level 10% of 2.36mm fine glass (FG) has slightly improved the strength characteristics. While, the results demonstrated decreasing in that properties for the concrete specimens contained on coarse glass (CG) up to 4.75mm. The maximum negative effect on compressive strength and modulus of rupture recorded at the ratio 30% of CG where was the reduction in compressive strength 28.52% opposite 22.12% for modulus of rupture at age of 28-day. From that results, it can be concluded that the effect of FG was little compared to GP.